ADSORPTION OF Ca(II), Pb(II) AND Ag(I) ON SULFONATO-SILICA HYBRID PREPARED FROM RICE HULL ASH - Siti Sulastri; Nuryono Nuryono; Indriana Kartini; Eko Sri Kunarti (Universitas Gadjah Mada, 2011)
In this research, adsorption of Ca(II), Pb(II) and Ag(I) in aqueous solution onto sulfonato-silica hybrid (SSH) prepared from rice hull ash (RHA) has been studied. The preparation of SSH adsorbent was carried out by oxidation of mercapto-silica hybrid (MSH) with hydrogen peroxide (H2O2) solution 33%. MSH was prepared, via sol-gel process, by adding 3 M hydrochloric acid solution to mixture of sodium silicate (Na2SiO3) solution and 3(trimethoxysilyl)-1-propanthiol (MPTS) to reach pH of 7.0. Solution of Na2SiO3 was generated from destruction of RHA with sodium hydroxide solution followed with heating at 500 °C for 30 min. The SSH produced was characterized with Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD) analyzer, energy dispersive X-ray (EDX) spectroscopy and determination of ion-exchange capacity for sodium ion (Na+). The adsorption of Ag(I) and Ca(II) were conducted in a batch system in various concentrations for one hour. The adsorbent ion was calculated based on difference of concentrations before and after adsorption process determined using atomic absorbance spectrophotometric (AAS) method. The adsorption character was evaluated using model of isotherm Langmuir and Freundlich adsorption to calculate the capacity, constants and energy of adsorption. Result of characterization by EDX and FTIR showed qualitatively that SSH has been successfully synthesized which were indicated by appearance of characteristic absorbance of functional group namely silanol (Si-OH), siloxane (Si-O-Si), methylene (-CH2-) and disappearance of mercapto group (SH). The XRD data showed amorphous structure of SSH, similar to silica gel (SG) and MSH. The study of adsorption thermodynamics showed that oxidation of MSH into SSH increases the ion-exchange capacity for Na+ from 0.123 to 0.575 mmol/g. The change in functional group from silanol to mercapto and from mercapto to sulfonato increases the adsorption capacity of Ca(II). However, the capacity order of adsorbents for both ions of Pb(II) and Ag(I) in aqueous solution is MSH > SG > SSH.